2012
DOI: 10.4322/natcon.2012.016
|View full text |Cite
|
Sign up to set email alerts
|

Gestão Eficiente de Bacias Hidrográficas no Brasil: Dificuldades e Perspectivas de Soluções

Abstract: Nas últimas décadas a preocupação com os indesejáveis resultados dos efeitos de atividades humanas sobre o meio ambiente aumentou consideravelmente. Toleram-se cada vez menos os problemas ambientais que interferem na qualidade de vida, especialmente a poluição dos corpos d'água, devido ao lançamento e acúmulo de efluentes industriais e esgotos domésticos sem tratamento. Os rios que banham metrópoles, a exemplo de São Paulo e Belo Horizonte, estão praticamente mortos: servem apenas como um canal por onde escoa … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 8 publications
0
4
0
1
Order By: Relevance
“…In recent decades, aquatic ecosystems have been significantly affected by multiple environmental impacts caused by the expansion of human activities (Budke et al, 2012;Chen et al, 2014;Mendoza et al, 2017). This has caused a disruption of the physical and chemical environment, has altered the natural dynamics of biological communities, led to environmental changes (Callisto et al, 2012;Tejerina & Malizia, 2012), and has significantly reduced the quality of the water and decreased aquatic biodiversity (Restello et al, 2014). Thus, aquatic ecosystems are among the most threatened ecosystems in the world (Harrison et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In recent decades, aquatic ecosystems have been significantly affected by multiple environmental impacts caused by the expansion of human activities (Budke et al, 2012;Chen et al, 2014;Mendoza et al, 2017). This has caused a disruption of the physical and chemical environment, has altered the natural dynamics of biological communities, led to environmental changes (Callisto et al, 2012;Tejerina & Malizia, 2012), and has significantly reduced the quality of the water and decreased aquatic biodiversity (Restello et al, 2014). Thus, aquatic ecosystems are among the most threatened ecosystems in the world (Harrison et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…A fish-based multimetric index is considered a low-cost and a rapid means of assessing ecological integrity in streams (Gonino et al, 2020). Moreover, with little training and as most people are familiar with local fish species even the community could volunteer and contribute to the monitoring process by reporting the occurrence or absence of key species (USEPA, 1997; Callisto et al, 2012;França & Callisto, 2017). It should be noted that the use of macroinvertebrates for biomonitoring has been more globally widespread than the use of fish (Rosenberg & Resh, 1993;Bae et al, 2005;Buss et al, 2015) and that this biotic group has been suggested as even more effective than fish at distinguishing reference from impacted sites in neotropical streams of Brazil (Ruaro et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…O planejamento da gestão de uma bacia hidrográfica deve propor uma visão que inclua as políticas públicas, as soluções tecnológicas e de educação ambiental a fim de promover o enfrentamento das problemáticas ambientais, a otimização de recursos e a garantia dos usos múltiplos da água. No entanto, as leis brasileiras reconhecem a qualidade da água tendo em vista apenas o seu grau de potabilidade e balneabilidade não considerando a integridade ecológica dos ecossistemas aquáticos que constituem as bacias hidrográficas (Callisto et al, 2012).…”
Section: Introductionunclassified